ISCHEMIC STROKE OF THE BRAINSTEM WITH INVOLVEMENT OF THE OCULOMOTOR NERVE NUCLEUS AS A MANIFESTATION OF A PERSISTENT FORAMEN OVALE A CASE REPORT OF A 40-YEAR-OLD PATIENT - Klahs, Krystyna; Nieradka, Kaja; Muraszko-Kuźma, Maciej; Twardy, Patryk; Wagner, Weronika; Białożyt, Jakub; Dębniak, Anna; Gutarowicz, Maciej; Modelewski, Patryk; Armatys, Michał (International Journal of Innovative Technologies in Social Science, 2026)
Aim: In our work, we want to emphasize the clinical importance of patent foramen ovale. It’s a potential cause of stroke in young patients without classic vascular risk factors. We want to feature the significance of transesophageal echocardiography in detecting foramen ovale and preventing stroke.Methods: We present a case of a young patient diagnosed with an atrial septal defect consistent with patent foramen ovale. Clinical presentation and diagnostic findings were analyzed, with particular attention to imaging modalities used in the evaluation of stroke etiology.Results: Patent foramen ovale, although asymptomatic, may lead to serious embolic complications, including stroke. In young patients without traditional risk factors, without showing any visible symptoms, the condition may cause serious damage. The use of transesophageal echocardiography significantly improves detection of interatrial shunts and allows for accurate diagnosis of structural cardiac abnormalities and prevention of stroke in young patients.Conclusions: Incorporating transesophageal echocardiography into the diagnostic workup of young patients prevents embolism from the foramen ovale. This approach can facilitate timely implementation of preventive strategies, including interventional closure, thereby reducing the risk of recurrent ischemic events, and should be added to screening protocols.